Membangun Sistem Informasi Administrasi Berbasis Web di RW. 024 Karangsatria, Tambun Utara Bekasi - Danny, Muhtajuddin; Muhidin, Asep; Butsianto, Sufajar; Triwibowo, Edi (Lentera Pengabdian, 2023)
Administrative services are very important and become a routine for village government. One of them is in the office of the Rukun Warga 024 Karangsatria Village, North Tambun, Bekasi. The importance of letter administration services in government agencies requires accuracy and service optimization, so that this letter administration service runs optimally and there should be no more errors and mistakes in carrying out this administrative service. With the development of information technology, it gives color to the author to create a web-based administrative information sistem at the Rukun Warga office 024 Karangsatria Village, Tambun Utara, Bekasi. This sistem will make it easy for the public to apply for letters such as a certificate of incapacity and a certificate of domicile, and also provide information.. Keywords: Administration, Web, PHP